Off-farm employment and spatial distribution of paddy farmers in integrated agricultural development area in north-west Selangor determined using GIS - Lokman, Eleanor Daniella (2015)
Most of the paddy farmers in Malaysia are earning low income from paddy plantation due to unstable yield, even the government invests heavily in the sector. The objective of this study is to investigate the involvement and location distribution of 250 paddy farmers and farm households in off-farm employment in IADA NWS using Geographic Information Systems (GIS) to capture a farm location effect on mobility with regional condition, such as to work or to the nearest town. The descriptive analysis was used to describe the respondent’s socio-economic profile. The relationship between off-farm participation and the independent variables identified were cross-tabulated. Chi-square was used to test the null hypothesis. The GIS was used to determine the spatial characteristics to off-farm participation in distinctive regions. Results shows The middle age group of 41-50 years old, SPM holders, have less than 5ha of paddy field and earn RM3,500 monthly of paddy farmers who are the majority to join off-farm employment. They usually get involved in agriculture activities including oil palm plantation, fisheries, fruits plantation, working with the government and doing own job.Spatially, the results indicated that most of the paddy farmers involved in off-farm job lives near to the town which in Kuala Selangor, as is less than ten (10) kilometres away from their house and paddy lot. The study shows that doing off-farm employment during their free time is an alternative strategy and has a potential to improve the income and well being of the paddy farmers and their family. Sharing farm and offfarm income of farmers could bring a big impact in the family. Furthermore, the diversification of employment in Malaysia however helps to smooth income by spreading risk across several activities.